2020
DOI: 10.1001/jamanetworkopen.2020.22787
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Electroacupuncture vs Sham Treatment on Change in Pain Severity Among Adults With Chronic Low Back Pain

Abstract: Key Points Question What is the effect of electroacupuncture vs sham treatment on pain severity in adults with chronic low back pain? Findings In this randomized clinical trial including 121 adults with chronic low back pain, there was no significant difference between real and sham electroacupuncture conditions in reduction in pain scores 2 weeks after treatment; however, real electroacupuncture resulted in statistically and clinically greater reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 64 publications
(129 reference statements)
1
28
0
Order By: Relevance
“…The researchers found statistically and clinically greater reduction of RMDQ in the verum, compared to the sham arm, in the prediction study. 9 However, this difference was not statistically significant in the mechanism study. 8 The contrasting results between the 2 studies could have been due to differences in the enrollment criteria, the lapses between enrollment and first treatment in the studies, treatment durations, or provider oversights.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The researchers found statistically and clinically greater reduction of RMDQ in the verum, compared to the sham arm, in the prediction study. 9 However, this difference was not statistically significant in the mechanism study. 8 The contrasting results between the 2 studies could have been due to differences in the enrollment criteria, the lapses between enrollment and first treatment in the studies, treatment durations, or provider oversights.…”
Section: Discussionmentioning
confidence: 74%
“…The second study (N = 102) developed and validated a prediction algorithm using reduction techniques from machine learning on a large number of baseline characteristics. 9 Inclusion criteria were people ages 21-65 with CLBP lasting >6 months, and no acupuncture within the past 3 years. Both studies 8,9 used the Roland Morris Disability Questionnaire (RMDQ) as the primary functional outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it has been reported that the symptoms worsened in patients with SDAVF in the prone position for a long time during spinal surgery (16,17), or after singing or standing for a long time (18,19). Electroacupuncture is a method of applying electrical stimulation with about 20 needles inserted in the prone position for about 20-30 min (20), and it is highly likely that the increase in intrathecal pressure caused by the prone position for a long time made the condition worse. In particular, since the patient was slightly overweight, this may have contributed to the worsening of his condition.…”
Section: Discussionmentioning
confidence: 99%